The Virtual River Game: Gaming using models to collaboratively explore river management complexity. (December 2020) - den Haan, R.J.; van der Voort, M.C.; Baart, F.; Berends, K.D.; van den Berg, M.C.; Straatsma, M.W.; Geenen, A.J.P.; Hulscher, S.J.M.H.
Abstract: Serious games are increasingly used as tools to facilitate stakeholder participation and stimulate social learning in environmental management. We present the Virtual River Game that aims to support stakeholders in collaboratively exploring the complexity of a changed river management paradigm in the Netherlands. The game uses a novel, hybrid interface design that features a bidirectional coupling of a physical game board to computer models. We ran five game sessions involving both domain experts and non-experts to assess the game's value as a participatory tool. The results show that the game was effective in enabling participants to collaboratively experiment with various river interventions and in stimulating social learning. As a participatory tool, the game appears to be valuable to introduce non-expert stakeholders to Dutch river management. We further discuss how the hybrid interface combines qualities usually found in board and computer games that are beneficial in engaging stakeholders and stimulating learning. Highlights: We developed a game as participatory tool to explore river management complexity. Game uses a physical board as a hybrid, bidirectional interface to computer models. Game was successful to engage domain experts and non-experts in five test sessions. Game is valuable to introduce non-expert stakeholders to Dutch river management. Hybrid interface combines board and computer game qualities to engage stakeholders.